Cucurak Tradition As A Family Communication Media For Welcoming Ramadan - Muslim, Muslim; Noegroho, Jati; Aminuddin, Ahsani Taqwim (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2023)
This study aims to determine the process and meaning of the Cucurak tradition as a communication medium in addition to the tradition of welcoming the month of Ramadan in the people of Bogor City. This research method is qualitative with a phenomenological approach through semi-structured interviews with eight informants to obtain field data. The results of this study found that food consumed as part of health is a reflection of the culture and blessings of the natural surroundings. In addition, the cucurak tradition is a moment of gathering with families who have been separated due to migrating and working/schooling outside the city. Cucurak is a moment for parents to convey messages and noble values to their children and grandchildren in the family. This traditional celebration is carried out as part of gratitude to God for longevity, health, and sustenance given. So that the cucurak tradition in this study is interpreted as a family communication medium, even the media communicates with God and Nature. Penelitian ini bertujuan untuk mengetahui proses dan pemaknaan tradisi Cucurak sebagai media komunikasi selain tradisi menyambut bulan Ramadhan di masyarakat Bogor. Metode penelitian ini adalah kualitatif dengan pendekatan fenomenologi melalui wawancara semi terstruktur dengan delapan narasumber untuk mendapatkan data lapangan. Hasil penelitian ini menemukan bahwa informan makanan yang dikonsumsi sebagai bagian dari kesehatan, cerminan budaya dan keberkahan alam sekitar. Selain itu tradisi cucurak menjadi momen berkumpul dengan keluarga yang telah terpisah karena merantau dan bekerja/sekolah di luar kota. Cucurak menjadi momen orang tua menyampaikan pesan dan nilai-nilai luhur kepada anak dan cucuk mereka dalam keluarga. Perayaan tradisi ini dilakukan sebagai bagian rasa syukur kepada Tuhan atas umur yang Panjang, kesehatan dan rezeki yang di berikan. Sehingga tradisi cucurak dalam penelitian ini dimaknai sebagai media komunikasi keluarga, bahkan media melakukan komunikasi dengan Tuhan dan Alam.